Profile kondisi tekanan darah dengan gaya hidup pada masyarakat RW 06 Kelurahan Sidomulyo Timur - Gaung Bebby Pithaloka; Vanessa Patria Pinandita; Ayulia Hermayuni; Yustina Yustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Hypertension or high blood pressure is a disease that causes very high mortality. Hypertension is a type of non-communicable disease that is chronic and can cause complications in body organs such as the heart, kidneys, brain and eyes. Hypertension is a disease that is strongly influenced by lifestyle such as sleep quality, stress, fat comsumption, and exercise. The purpose of this service is to determine the condition of blood pressure with lifestyle in the community of RW 06 Sidomulyo Timur Pekanbaru. The design of this service is descriptive correlation using a cross sectional approach. The objects in this service are adults in RW 06 Sidomulyo Timur with a sample of 30 people taken using quota sampling technique. The method of collecting data is through interviews and direct hypertension checks. The people of RW 06 Sidomulyo Timur Pekanbaru who experience stress (13.33%), poor sleep quality (3.4%), consume fat (46.67%), and exercise regularly (50%). In this study, the results showed that there was a relationship between lifestyle and blood pressure conditions. The condition of blood pressure in the community of RW 06 Sidomulyo Timur is related to lifestyle, including: stress, sleep quality, fat consumption and exercise.